Challenges in Serious Game Design and Development: Educators’ Experiences - Dimitriadou, Anastasia; Djafarova, Naza; Turetken, Ozgur; Verkuyl, Margaret; Ferworn, Alexander (Simulation & gaming, 2021)
Background. Relatively little is known about the role of educators in serious game design and development and their experiences with serious game implementation. We investigate educators’ perceived challenges deriving from their involvement as subject matter experts during the serious game development trajectory. Methods. A secondary analysis of data collected through an exploratory survey about serious game design and development approaches was carried out. The sample included 41 educators from post-secondary education institutions across North America. An in-depth analysis of qualitative data revealed educators’ roles in game development, the challenges they faced, and the strategies they deployed in serious game design, development, and implementation. Results. Educators, as serious game designers, perceived challenges to be administrative, design-related, attitudinal, and communicative. Strategies deployed to overcome challenges during the concept development, pre-production, and production stages of game design include the creation of games that balance learning and fun, and enhanced team collaboration through cultural mediation. During the post-production stage, although challenges are acknowledged and some strategies, such as improving the usability of a game, are deployed, a clear pattern in challenges and mitigating strategies could not be observed. Conclusion. Serious game design and development can be improved by nurturing diversity of ideas and adopting creative design and development methodologies. Serious game implementation can be improved by devising effective administrative and attitudinal strategies, and incorporating diversity of ideas into target curricula. Additionally, clear directives about usability should be devised, and academic objectivity towards serious games needs to be be created. Strategies to achieve these goals should focus on developing trust between target users, the technical development team, and educators as serious game implementers.